2020
DOI: 10.2355/isijinternational.isijint-2019-230
|View full text |Cite
|
Sign up to set email alerts
|

Growth Behavior of a Mechanically Long Fatigue Crack in an FeCrNiMnCo High Entropy Alloy: A Comparison with an Austenitic Stainless Steel

Abstract: The fatigue crack growth characteristics of an Fe20Cr20Ni20Mn20Co high-entropy alloy (HEA) were investigated by ΔK increasing compact tension test in comparison with SUS316L. The fatigue crack growth rate of the HEA was lower than that of the SUS316L. The predominant crack growth path was the grain interior for both alloys. A difference was observed in the crack roughness; i.e., the fatigue crack growth path of the HEA was more distinctly deflected than that of the SUS316L. This indicates that roughnessinduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In FeCrNiMnCo alloys, MnCr2O4 spinel, Al-and Si-rich oxides, MnS and Cr-rich M23C6 particles have been reported to form [11,21,48]. In the present work, oxides including Mn, Cr, and Al were observed as the alloys contain Al as an impurity element.…”
Section: Characterization Of Non-metallic Inclusionssupporting
confidence: 50%
See 1 more Smart Citation
“…In FeCrNiMnCo alloys, MnCr2O4 spinel, Al-and Si-rich oxides, MnS and Cr-rich M23C6 particles have been reported to form [11,21,48]. In the present work, oxides including Mn, Cr, and Al were observed as the alloys contain Al as an impurity element.…”
Section: Characterization Of Non-metallic Inclusionssupporting
confidence: 50%
“…The previous researchers revealed that the HEAs have possibilities to achieve excellent combinations of strength and ductility compared to conventional structural alloys such as stainless steel, twinning-induced plasticity (TWIP) steels, and transformation-induced plasticity (TRIP) steels [6,7]. The equiatomic FeCrNiMnCo alloy, the most extensively studied HEA, shows a high phase stability as a FCC single phase for a wide range of temperatures as well as an excellent strength under cryogenic conditions [2,[8][9][10][11][12]. Thus, it is considered as a promising cryogenic material.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Mizumachi et al observed the propagation feature of fatigue cracks in Fe 20 Cr 20 Ni 20 Mn 20 Co 20 HEA. 6 Thurston et al studied the SCC propagation mechanism of CrMnFeCoNi HEAs and they reported a change of crack propagation mechanism from transgranular crack propagation at room temperature to intergranular-dominated failure at lower temperatures. 7 To further improve the reliability of HEAs and expand its applications, in-deep insights into the SCC mechanisms of HEAs are strongly desired, comprising atomic-scale deformation mechanisms and chemical reactions with corrosive environments.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [22,23] reported that the threshold stress intensity range, ΔK th , decreased with increasing force ratio, as is the case for conventional alloys. Mizumachi et al [24] reported that the fatigue-crack propagation rate for CrMnFeCoNi alloy is lower than that for the 316L austenitic stainless steel because of crack closure from deflected crack growth. In contrast, austenitic stainless steel has a high effective threshold stress intensity range, ΔK eff,th .…”
mentioning
confidence: 99%